Efficacy and Cost-Effectiveness Analysis of Internet-Based Cognitive Behavioral Therapy for Obsessive-Compulsive Disorder: Randomized Controlled Trial - Yiwen Wu; Xin Li; Yuxin Zhou; Rui Gao; Kaifeng Wang; Huiling Ye; Na Lyu; Chun Wang; Ning Zhang; Zhen Wang; Qing Fan (JMIR Publications, 2023)
BackgroundObsessive-compulsive disorder (OCD) is a common and chronic mental illness with a high rate of disability. Internet-based cognitive behavioral therapy (ICBT) makes online treatment available to patients and has been shown to be effective. However, 3-arm trials on ICBT, face-to-face cognitive behavioral group therapy (CBGT), and only medication are still lacking. ObjectiveThis study is a randomized, controlled, assessor-blinded trial of 3 groups for OCD: ICBT combined with medication, CBGT combined with medication, and conventional medical treatment (ie, treatment as usual [TAU]). The study aims to investigate the efficacy and cost-effectiveness of ICBT related to CBGT and TAU for adults with OCD in China. MethodsIn total, 99 patients with OCD were selected and randomly assigned to the ICBT, CBGT, and TAU groups for treatment for 6 weeks. The primary outcomes were the Yale-Brown Obsessive-Compulsive Scale (YBOCS) and the self-rating Florida Obsessive-Compulsive Inventory (FOCI), compared at baseline, during treatment (3 weeks), and after treatment (6 weeks), to analyze efficacy. The secondary outcome was the EuroQol Visual Analogue Scale (EQ-VAS) scores of the EuroQol 5D Questionnaire (EQ-5D). The cost questionnaires were recorded to analyze cost-effectiveness. ResultsRepeated-measures ANOVA was used for data analysis, and the final effective sample size was 93 (ICBT: n=32, 34.4%; CBGT: n=28, 30.1%; TAU: n=33, 35.5%). After 6-week treatment, the YBOCS scores of the 3 groups significantly decreased (P<.001), and there were no significant differences among groups. The FOCI score of the ICBT (P=.001) and CBGT (P=.035) groups was significantly lower than that of the TAU group after treatment. The total cost of the CBGT group (renminbi [RMB] 6678.45, 95% CI 4460.88-8896.01 [US $1010.36, 95% CI 678.87-1345.84]) was significantly higher than that of the ICBT group (RMB 3308.81, 95% CI 2476.89-4140.73[US $500.58, 95% CI 374.72-626.43], P<.001) and the TAU group (RMB 2259.61, 95% CI 2074.16-2445.05 [US $341.85, 95% CI 313.79-369.90], P<.001) after treatment. The ICBT group spent RMB 303.19 (US $45.97) less than the CBGT group and RMB 11.57 (US $1.75) less than the TAU group for each unit reduction in the YBOCS score. ConclusionsTherapist-guided ICBT combined with medication is as effective as face-to-face CBGT combined with medication for OCD. ICBT combined with medication is more cost-effective than CBGT combined with medication and conventional medical treatment. It is expected to become an efficacious and economic alternative for adults with OCD when face-to-face CBGT is not available. Trial RegistrationChinese Clinical Trial Registry ChiCTR1900023840; https://www.chictr.org.cn/showproj.html?proj=39294